Indium-Mediated Cleavage of the Trityl Group from Protected 1H-Tetrazoles - Behloul, Cherif; Bouchelouche, Kenza; Guijarro, David; Foubelo, Francisco; Nájera, Carmen; Yus, Miguel (Synlett, 2015)
On treatment with indium metal in MeOH–THF, trityl groups undergo reductive removal from 1H-protected tetrazoles (including aliphatic, aromatic, and heteroaromatic substituents), affording the corresponding free tetrazoles in excellent yields, without any decomposition of the tetrazole ring or reduction of any other group.
Keywords: tetrazole; indium; detritylation; cleavage